Uterine tumors resembling ovarian sex cord tumors (UTROSCT) with metastasis: clinicopathological study of two cases - Umeda, Shigeaki (e-Century Publishing Corporation, 2014)
Uterine tumors with sex cord-like elements are divided in two groups; uterine tumors resembling ovarian sex cord tumors (UTROSCT), and endometrial stromal tumors with sex cord-like elements (ESTSCLE). UTROSCT is currently defined as the neoplasm predominantly or exclusively composed of sex cord-like elements, and generally behaves in a benign fashion. We studied two unusual cases of UTROSCT with metastasis. One case was a 38-year-old multiparous woman presented with hypermenorrhea. The tumor grew as an intramural mass, and metastasized to a pelvic lymph node. Another case was a 57-year-old woman presented with genital bleeding. The tumor grew as a submucosal exophytic mass, and metastasized to the epiploic appendix. Microscopic examination of the 2 cases revealed that they were composed of sex cord-like cells, epithelioid cells and spindle cells. They exhibited solid pattern in predominance. Both solid and sex cord-like elements showed similar immunoreactivities for more than 3 sex cord markers, but simultaneously showed different staining patterns for some other markers. Characteristic features of endometrial stroma such as tongue-like infiltration and spiral arteries-like arterioles were not observed. RT-PCR analysis confirmed the absence of JAZF1-SUZ12 gene fusion, supporting the histopathological diagnosis of UTROSCT rather than ESTSCLE. The current cases warned the potential risk of UTROSCT whose biological behavior is still uncertain. We discuss histopathological, immunohistochemical and molecular findings of UTROSCT with metastasis.